Hello!
The inverse of functions are the relation found by interchanging the domain and range of a given function. This means that we switch the y and x variables in the given function and solve for y.
It would look like this when we change it: x = 3(y + 2) - 4. Then, we need to solve for y.
x = 3(y + 2) - 4 (add 4 to both sides)
x + 4 = 3(y + 2) (divide both sides by 3)
(x + 4)/3 = y + 2 (subtract 2 from both sides)
(x + 4)/3 - 2 = y
y = (x + 4)/3 - 2
Therefore, the inverse of f(x) is
. Now, we need solve for the y-values when x is equal to 2, which means we need to substitute "2" into the given function.
f(x) = (2 + 4)/3 - 2 (simplify)
f(x) = (6)/3 - 2 (divide)
f(x) = 2 - 2 (simplify)
f(x) = 0
Therefore, your answer is the second choice, zero.